Investigation of the inhibitory properties of azo-dyes on chorismate synthase from Paracoccidioides brasiliensis - Katharina Fuchs; Massimo G. Totaro; Marina Toplak; Aleksandar Bijelic; Peter Macheroux (Journal of Enzyme Inhibition and Medicinal Chemistry)
The efficient inhibition of 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) by the broad-spectrum herbicide glyphosate validates the shikimate pathway as a promising target for developing antimicrobial, fungicidal and herbicidal agents. The last enzyme of this pathway, chorismate synthase (CS), catalyses an unusual reaction, making it an attractive target for novel inhibitors. Therefore, we tested a series of azo-dyes for their inhibitory potential against CS from the pathogenic fungus Paracoccidioides brasiliensis (PbCS) and identified the azo-dye PH011669 that exhibits a dissociation (Kd) and 50% inhibitory constant (IC50) of 1.1 ± 0.1 and 10 ± 1 µM, respectively. Molecular docking and MD simulations provided insight into the mode of inhibition, showing that PH011669 binds to the enzyme’s active site primarily through electrostatic interactions. Thus, our study is the first to integrate structural and computational methods to guide future efforts towards designing the next generation of CS inhibitors.